The Effect of Exclusive Breastfeeding on Toddlers' Pneumonia Cases in Surabaya - Sasi Riyadinil Ula; Retno Adriyani (Universitas Airlangga, 2019)
Background: Pneumonia is one of the most common causes of illness in infants. Exclusive breastfeeding is one of the many factors associated with pneumonia cases in infants. The discovery of pneumonia cases in toddlers in East Java increased from 2013 to 2016, the highest case finding in Surabaya precisely at the Sememi health service center (PUSKESMAS) about 281 toddlers. Purpose: To analyze the effect of exclusive breastfeeding and other factors on pneumonia cases in infants in PUSKESMAS Sememi, Benowo Subdistrict, Surabaya. Methods: This study is an observational analytic study with a case-control approach. The control sample and the cases are consisting of 35 samples from the total population counting 61 toddlers. In this study, the sampling technique was a simple random sampling. The study was conducted in Sememi health service center, Benowo Subdistrict, Surabaya from February to November 2018. The variables studied included the characteristics of children (age and gender) and other factors namely exclusive breastfeeding, nutritional status, birth weight, immunization status, administration of vitamin A and history of asthma. Data were analyzed descriptively and analytically using binary logistic regression statistical tests. Results: There was a significant influence between exclusive breastfeeding (p= 0.00; OR= 4.18; 95% CI= 1.54<OR<11.34) for pneumonia cases in toddlers. Other factors including low birth weight, nutritional status, immunization status, administration of vitamin A, asthma history does not affect pneumonia cases in toddlers. Conclusion: Exclusive breastfeeding can prevent pneumonia cases in toddlers.